ANALISIS BIAYA PRODUKSI DAN HARGA JUAL CPO (CRUDE PALM OIL) DALAM MENINGKATKAN LABA BERSIH PADA PT DAMAI JAYA LESTARI - Julfikar, Julfikar; Sabarudin, Sabarudin; Syahrir, Sasmita Nabila (Jurnal Akuntansi Kompetif, 2025)
This study aims to examine how production costs and selling prices of CPO influence the net profit of PT Damai Jaya Lestari. A qualitative research approach is utilized, employing both primary and secondary data sources. Data collection was conducted through interviews, documentation, and review of financial reports concerning production costs and selling prices of CPO. The analysis was performed using descriptive methods; the qualitative descriptive technique was applied to portray the actual condition of the research subject based solely on observable facts. The findings reveal that annual production costs tend to rise due to high expenditures incurred during the production process, consequently leading to an increase in the quantity of CPO available for sale. Similarly, the selling prices of CPO have also escalated annually as production volumes grow, and increased sales revenue consequently bolsters the net profit achieved by the company. In summary, production costs and the volume-based selling price of CPO both exert an impact on the net profit. Keywords: Production Costs, Selling Prices and Net Profit.